SARS-Cov-2 in peritoneal fluid: an important finding in the Covid-19 pandemic. Issue 10 (20th July 2020) - Barberis, A; Rutigliani, M; Belli, F; Ciferri, E; Mori, M; Filauro, M
Fundings: no funding to declare regarding this study.